Innovative methods for safeguarding cultural heritage - Themistocleous, Kyriacos (My University, 2025)
Cultural heritage sites constitute irreplaceable records of human history, illustrating the progression of our social, architectural, and cultural practices. Increasing threats from climate-related hazards, such as shifting rainfall patterns, escalating temperatures, and intensified extreme weather, combined with geological and physical risks like landslides, earthquakes, and erosion, render these sites increasingly vulnerable. Earth observation technology is pivotal in preserving cultural heritage by improving documentation, enabling more effective monitoring, and supporting proactive conservation strategies. Recently, with advances in technology, advanced 3D scanning and imaging techniques, such as laser scanning and photogrammetry, have captured precise digital records of cultural heritage sites, documenting and helping conservators measure changes over time and swiftly identify structural vulnerabilities. Remote sensing technologies, including satellite imagery, aerial photography and UAV-based surveys, allow for extensive site evaluations, reducing risks and costs associated with onsite inspections, especially in remote or hazardous locations. Methodological frameworks and technological developments, encompassing remote sensing, satellite and aerial imaging, digital modeling with laser scanners, photogrammetry, and participatory data collection, are creating fresh opportunities for proactive, evidence-based conservation. Data-driven tools such as sensor arrays and digital twin models enable continuous monitoring, where real-time structural and environmental information is integrated into predictive models to anticipate emerging threats. This paper provides a comprehensive review of innovative remote sensing methods for safeguarding and monitoring cultural heritage under these compounded vulnerabilities. It focuses on integrating techniques employing remote sensing, geodetic methodologies, synthetic aperture radar, unmanned aerial vehicles (UAVs), digital twin platforms, and participatory data collection initiatives with sensors and crowdsourcing. A key emphasis of this study is the integration of state-of-the-art techniques for monitoring cultural heritage assets. Examples of various studies conducted in Cyprus, more specifically the case study of the Neolithic UNESCO World Heritage Site of Choirokoitia, demonstrate the practical application of these frameworks, highlighting the TRIQUETRA project (funded by the EU Horizon Europe research and innovation programme) with an innovative integration of conventional and novel methodologies for risk quantification, site monitoring, and stakeholder participation. The findings underscore the critical necessity of interdisciplinary collaboration, sustained funding mechanisms, and robust policy support to ensure the long-term preservation of cultural heritage for future generations.
Keywords: Cultural Heritage; Climate change; Remote Sensing; digital twins; crowdsourcing; virtual reality; photogrammetry